2019
DOI: 10.1111/1365-2664.13542
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and economic benefits of low‐intensity urban lawn management

Abstract: Intensive management of urban lawns is globally widespread, predominantly for aesthetic reasons. However, a growing body of knowledge demonstrates negative ecological and environmental effects of this practice. We present a meta‐analysis of North American and European studies from 2004 to 2019, which incorporates three previously unpublished datasets from eastern Canada, to investigate how mowing intensity impacts the ecology of urban lawns. The meta‐analysis provides aggregated evidence that invertebrate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 57 publications
3
34
0
Order By: Relevance
“…Although our cost estimates are therefore not directly transferable to other communities, the cost differences between the vegetation types we studied are consistent with other sources of information, which indicate-for roadside vegetation-considerably lower costs for the maintenance of "landscape lawns" than for frequently mown "utility lawns" (three times more expensive than landscape lawns) or woody areas (six times more expensive) [159]. Therefore, our cost estimates confirmed that wildflower meadows can be a promising option not only to increase the value of green spaces for biodiversity [18], but also to reduce maintenance costs [26,48,160]. This fact may lead to an increased planting of urban flower meadows in the future, since in addition to positive effects on biodiversity and contextdependent considerations of aesthetics and public perception, human resources and economic sustainability are important [48].…”
Section: Costs Of Green Space Maintenancesupporting
confidence: 87%
“…Although our cost estimates are therefore not directly transferable to other communities, the cost differences between the vegetation types we studied are consistent with other sources of information, which indicate-for roadside vegetation-considerably lower costs for the maintenance of "landscape lawns" than for frequently mown "utility lawns" (three times more expensive than landscape lawns) or woody areas (six times more expensive) [159]. Therefore, our cost estimates confirmed that wildflower meadows can be a promising option not only to increase the value of green spaces for biodiversity [18], but also to reduce maintenance costs [26,48,160]. This fact may lead to an increased planting of urban flower meadows in the future, since in addition to positive effects on biodiversity and contextdependent considerations of aesthetics and public perception, human resources and economic sustainability are important [48].…”
Section: Costs Of Green Space Maintenancesupporting
confidence: 87%
“…In particular, reduced mowing of lawns is a simple action that can benefit pollinators by increasing the availability of floral and larval food sources (Watson et al, 2020). Whilst reduced mowing is perceived as untidy by some portions of the public, a recent…”
Section: Opportunities For Increasing Uptake Of Pollinator Conservamentioning
confidence: 99%
“…Urban grasslands encompass a wide range of different types, from short-cut and sometimes irrigated lawns with ornamental and recreational functions to less-intensively managed tall-grass meadows (Figure 1; Tables S1 and S2; Rudolph et al, 2017;Sehrt, Bossdorf, Freitag, & Bucharova, 2020). Tall-grass meadows are typically mown once or twice per year in late summer and can provide habitat for native plants and animals (Cilliers et al, 2004;Norton et al, 2019;Watson, Carignan-Guillemette, Turcotte, Maire, & Proulx, 2020). Converting lawns to meadows significantly increases their value for biodiversity (Chollet, Brabant, Tessier, & Jung, 2018;Wastian, Unterweger, & Betz, 2016) and bene-fits ecosystem functions such as pollination or heat regulation (Ignatieva & Hedblom, 2018).…”
Section: Introductionmentioning
confidence: 99%